2019
DOI: 10.1002/anie.201812708
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Organic Supramolecular Box as a Universal Reservoir of UV, WL, and NIR Light for Long‐Persistent Luminescence

Abstract: Long persistent luminescence (LPL) materials have au nique photophysical mechanism to store light radiation energy for subsequent release.H owever,i nc omparison to the common UV source,w hite-light (WL) and near-infrared (NIR) excited LPL is scarce.Herein we report ametal-organic supramolecular boxbased on aD-p-A-type ligand. Owing to the integrated one-photon absorption (OPA) and two-photon absorption (TPA) attributes of the ligand, the heavy-atom effect of the metal center,a sw ell as p-stackinga nd Jaggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 20 publications
0
67
0
Order By: Relevance
“…Alternatively, two-photon absorption (TPA) utilizes the near-infrared (NIR) wavelengths that are more accessible for biological sciences due to higher spatial resolution, less phototoxicity and deeper tissue penetration. 16,17 Although progress has been made, systems exhibiting twophoton-induced ultralong emission are limited to inorganic and organic-inorganic hybrid materials, [18][19][20][21] and two-photonexcited ultralong organic room temperature phosphorescence (TPUOP) materials from purely organic single component materials are unfortunately not yet discovered. The design and synthesis of TPUOP materials still remains a challenge because of the lack of efficient molecular design strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, two-photon absorption (TPA) utilizes the near-infrared (NIR) wavelengths that are more accessible for biological sciences due to higher spatial resolution, less phototoxicity and deeper tissue penetration. 16,17 Although progress has been made, systems exhibiting twophoton-induced ultralong emission are limited to inorganic and organic-inorganic hybrid materials, [18][19][20][21] and two-photonexcited ultralong organic room temperature phosphorescence (TPUOP) materials from purely organic single component materials are unfortunately not yet discovered. The design and synthesis of TPUOP materials still remains a challenge because of the lack of efficient molecular design strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported a new type of metal-organic frameworks (MOFs) with long-lasting afterglow which showed highly tunable afterglow phosphorescence colors upon pyridine solution treatment. This finding supplies a group of MOFs-based persistent luminescence nanophosphors with high performance [150][151][152][153][154]. Up to now, the afterglow MOFs have not been used in biomedical fields in vivo due to the relatively short emission wavelength and the undesirable diameter.…”
Section: New Organic and Polymeric Plnps With Long Afterglow For In Vmentioning
confidence: 72%
“…4‐(9H‐Carbazol‐9‐yl)‐phenyl‐2,3′:6′,3″‐terpyridine (Caz‐PhTpy) was synthesized in two steps via reported methods for reference. [ 22,23 ] (see Scheme S1, Supporting Information, for preparation details). The as‐prepared microcrystalline sample was named as Powder and characterized by 1 H NMR, IR, and MS spectra (Figures S1–S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%